2023
DOI: 10.3390/en16041658
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Systematic Literature Review on the Contribution of Hydrogen to Universal Access to Energy in the Rationale of Sustainable Development Goal Target 7.1

Abstract: As part of the United Nations’ (UN) Sustainable Development Goal 7 (SDG7), SDG target 7.1 recognizes universal electrification and the provision of clean cooking fuel as two fundamental challenges for global society. Faltering progress toward SDG target 7.1 calls for innovative technologies to stimulate advancements. Hydrogen has been proposed as a versatile energy carrier to be applied in both pillars of SDG target 7.1: electrification and clean cooking. This paper conducts a semi-systematic literature review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…For example, SDG 7 aims to ensure access to affordable, reliable, sustainable, and modern energy. Implementing green hydrogen technology in kitchens would help reduce dependency on fossil fuels and promote the use of clean and renewable energies [46]. Additionally, aligning with SDG 9, which emphasizes innovation and sustainable infrastructure, developing green hydrogen kitchens could foster technological innovation and stimulate the economy through job creation in emerging sectors.…”
Section: Resultsmentioning
confidence: 99%
“…For example, SDG 7 aims to ensure access to affordable, reliable, sustainable, and modern energy. Implementing green hydrogen technology in kitchens would help reduce dependency on fossil fuels and promote the use of clean and renewable energies [46]. Additionally, aligning with SDG 9, which emphasizes innovation and sustainable infrastructure, developing green hydrogen kitchens could foster technological innovation and stimulate the economy through job creation in emerging sectors.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we adopted a semisystematic approach that combines a structured core methodological element with the flexibility to narratively discuss spontaneously emerging content [50]. The key steps to achieve a more consistent result are proposed by Grant and Booth [51], who defined four sequential steps: Search, Appraisal, Synthesis, and Analysis (SASA) [50].…”
Section: Methodology and Approachmentioning
confidence: 99%
“…The usage of hydrogen energy for rural electrification was found to be possible after Schöne did a review on hydrogen and its capability towards universal access to energy [29]. It was found that hydrogen can be used as a backup energy supply for small-scale off-grid villages.…”
Section: Hydrogen Energymentioning
confidence: 99%